2013
DOI: 10.1515/fhep-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Economic Perspectives on Personalized Health Care and Prevention

Abstract: The objective of this paper is to provide an overview of economic evaluation of personalized medicine, focusing particularly on the use of costeffectiveness analysis and other methods of valuation. We draw on insights from the literature and our work at the University of California, San Francisco Center for Translational and Policy Research on Personalized Medicine (TRANSPERS). We begin with a discussion of why personalized medicine is of interest and challenges to adoption, whether personalized medicine is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…Thus, our research group is developing approaches to assessing the value of these new technologies given the complexities they raise, such as the results they may provide on conditions that are not treatable (http://pharmacy.ucsf.edu/news/2013/03/11/1/). 25 Our work has shown that stakeholders, such as health payers, want a broad range of information on new technologies in order to promote informed coverage decisions. 36 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, our research group is developing approaches to assessing the value of these new technologies given the complexities they raise, such as the results they may provide on conditions that are not treatable (http://pharmacy.ucsf.edu/news/2013/03/11/1/). 25 Our work has shown that stakeholders, such as health payers, want a broad range of information on new technologies in order to promote informed coverage decisions. 36 …”
Section: Discussionmentioning
confidence: 98%
“…Future research should also consider examining other approaches to measuring values, which have not to date been used widely to examine personalized medicine, such as budget-impact analysis, value-of-information analysis, stated choice, and willingness-to-pay methods. 24,25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reviews have explored different aspects of the challenges affecting the evaluation of pharmacogenetics. Phillips et al 14 presented a detailed overview of various aspects relating to economic evaluations of personalized medicine, and highlighted six areas for future research, ranging from applying existing methods to assessments of personalized medicine to developments of new conceptual frameworks and methods specific to these technologies. Godman et al 15 discussed current knowledge of the value of personalized medicine and concerns relating to personalized medicine from a payer’s perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Данный показатель является необходимым звеном в оценке функционирования системы здравоохране-ния в целом, отдельных ее подразделений и структур, а также экономическим обоснованием мероприятий по охране здоровья населения [11][12][13][14].…”
Section: перспективы персонализированной педиатрии как глобального инunclassified